Supporting students with special needs in virtual and hybrid inclusive classrooms: Perceptions and practices from the U.S. during the COVID-19 pandemic - Norrmén-Smith, J (2021)
Throughout the COVID-19 pandemic, public school students with special needs in the United States were legally entitled to individualized support in the least restrictive environment deemed possible, which for some, meant inclusion in mainstream classrooms. Although the literature on inclusion in physical classrooms is extensive, research on inclusive digital education in virtual and hybrid spaces is lacking. This study investigates how teachers attempted to engage in inclusive pedagogical practice in digitally mediated classrooms. In doing so, it provides novel insights into the perceived academic and social impacts of these pedagogical changes on the educational experiences of students with special needs. Grounded in the theoretical framework of inclusive research, this mixed methods study elevates the voices of students with special needs, their teachers, and their parents through interviews and a survey to illustrate how inclusive education was interpreted and delivered over the course of pandemic. Situating the study at the nexus of digital equity and inclusive special education, the research discusses the multidimensional digital divide that disproportionately affects students with intersecting marginalized identities, such as those in this study’s sample. Ultimately, the research addresses broader questions about the conflicting values in inclusion, the variability of inclusive practice, and the challenging considerations for designing and delivering inclusive special education in virtual and hybrid learning spaces.